Coordinated and interactive operating method of intelligent device - YANG YIFENG (2017)
The invention relates to a coordinated and interactive operating method of an intelligent device, which comprises a means of connection, a means of collection, a means of work division, a means of back transmission and a means of updating and optimization, and is characterized in that the means of connection refers that electronic devices are connected with a cloud processing assembly or a local work division processing master control terminal; the means of collection refers that user information is collected through sensors of the electronic devices; the means of work division refers that the collected information is transmitted to the cloud processing assembly or the local work division processing master control terminal, and then the information is handed to a cloud data center to operate or divided to each electronic device to process; the means of back transmission refers that the information processed by the means of work division is transmitted back to the cloud processing assembly to the local work di